Dietary Zn and Human Health - Elad Tako (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
• Zinc (Zn) is an essential micronutrient that contributes to the proper functioning of over 300 enzymes and multiple biochemical and structural processes in the body. Zinc functions in the regulation of an extensive variety of genes, such as those involved in nucleic acid metabolism, cell signalling, apoptosis, and plays an integral role in immune system functioning. Even a mild Zn deficiency can profoundly affect growth and development, as well as impede immune differentiation and maturation. Zinc is widely distributed in foods, however, it was demonstrated that dietary constituents, such as phytate, polyphenols, and the intestinal microbiome, affect its dietary bioavailability and intestinal absorption. Regulation of zinc metabolism is achieved through a balance of absorption and excretion and involves adaptive mechanisms. The aim of this Special Issue is to explore dietary approaches that aim to improve Zn bioavailability and absorption, biomarkers of status, and the effect of Zn status on the intestinal microbiome.